Myocardial injury in COVID-19: A case series - Pratiti Choudhuri; Ira Balakrishnan M; Udismita Baruah; Kapil Gupta (Asian Journal of Medical Sciences, 2023)
The COVID-19 pandemic has affected nearly millions of populations worldwide. The range of symptomatology is vast, though predominantly respiratory, and ranges from mild flu-like symptoms to severe respiratory illness with acute respiratory distress syndrome. COVID-19 is associated with many non-respiratory complications affecting the heart, kidneys, gastrointestinal system, central nervous system, and blood vessels. Myocardial injury in COVID-19 patients has varied presentations ranging from arrhythmias, myocardial infarction, myocarditis, and cardiomyopathy to cardiogenic shock. It is usually associated with elevated levels of cardiac biomarkers, with or without any changes in electrocardiography or cardiac imaging. Diagnosis may be difficult based on clinical symptoms or electrocardiogram changes alone, and it can be made using 2D echocardiography, coronary angiogram, CT coronary angiogram, or cardiac magnetic resonance imaging, depending on clinical suspicion. COVID-19-associated cardiac injury increases overall morbidity and mortality. In this case series, five COVID-19 cases with different cardiac manifestations were reported with the intention of presenting the various manifestations of cardiac complications, the course of the disease, and the challenges associated with the complications. This case series showed that cardiac complications are common in the 2nd week during the cytokine storm phase, and timely case-specific specialized diagnostic and therapeutic cardiac interventions might improve the chances of patient survival.